2016
DOI: 10.1016/j.jceh.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Transmission from Living Donor to Recipient in Liver Transplantation: A Case Report

Abstract: Many infections are transmitted from a donor to a recipient through organ transplantations. The transmission of dengue virus from a donor to a recipient in liver transplantation is a rare entity, and currently, there is no recommendation for screening this virus prior to transplantation. We report a case of transmission of dengue virus from donor to recipient after liver transplantation. The recipient had a history of multiple admissions for hepatic encephalopathy and ascites. He was admitted in the ICU for 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…This apparent discrepancy might be due to inadequate sample size. Furthermore, in some centers, cases that are associated with less severe disease (e.g., transient bacteremia that responds quickly to therapy) are likely to be under-recognized and, therefore under-reporting may be significant [ 27 ]. Furthermore, a thorough review of cultures for all kidney recipients of organs from DCD donors has now been implemented at our institute.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy might be due to inadequate sample size. Furthermore, in some centers, cases that are associated with less severe disease (e.g., transient bacteremia that responds quickly to therapy) are likely to be under-recognized and, therefore under-reporting may be significant [ 27 ]. Furthermore, a thorough review of cultures for all kidney recipients of organs from DCD donors has now been implemented at our institute.…”
Section: Discussionmentioning
confidence: 99%
“…According to published data, CHIKV in solid organ transplant recipients seems to have a benign course and favorable outcome (19,20), whereas data for DENV in these patients are less clear. Case descriptions report uncomplicated outcomes, whereas a recent literature review reported a significantly higher incidence of severe dengue and a higher mortality rate among transplant patients with dengue (21)(22)(23). A recent report of DENV, ZIKV, and CHIKV infections diagnosed in hematopoietic stem cell transplant recipients and oncohematologic patients found prolonged viremia in those with DENV and viruria in those with ZIKV; the most common complication was thrombocytopenia, but all patients survived without sequelae (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that dengue diagnosis among SOT recipients could be difficult because of the immunosuppressive regimen that may mask dengue symptoms. 17,26 In addition, the symptoms can be attributed to comorbidities, opportunistic infections, or the adverse effects of some immunosuppressive drugs, 27,28 all of which can delay dengue diagnosis with the subsequent deterioration of patient outcomes. Thus, in regions where the virus is endemic, dengue should be suspected early in SOT recipients and opportunely evaluated by infectious diseases specialist and a timely critical care unit access should be assured.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%